Neonatal circumcision in severe haemophilia: a survey of paediatric haematologists at United States Hemophilia Treatment Centers. (4th December 2014) - Kearney, S.; Sharathkumar, A.; Rodriguez, V.; Chitlur, M.; Valentino, L.; Boggio, L.; Gill, J.
Summary Neonatal circumcision in patients with severe haemophilia has not been well studied. We performed a survey of paediatric haematologists from Hemophilia Treatment Centers (HTC) across the United States to better understand the attitudes toward and management of neonatal circumcision in haemophilia patients. Response rate to our survey was 40% (n = 64/159). Thirty‐eight percent of respondents (n = 24) said that they would allow this procedure in the newborn period but in many cases this was against medical advice. The most reported concern regarding neonatal circumcision in haemophilia patients was the risk of development of an inhibitor (n = 25; 39%) followed by the concern for bleeding (n = 22; 34%) and issues related to vascular access in the neonate (n = 11; 17%). All respondents recommended at least one preprocedure dose of factor replacement. Twenty‐two percent (n = 14) of respondents did not use more than one dose of factor replacement but 32% (n = 21) used 1–2 postoperative doses. The remainder of paediatric haematologists surveyed recommended between 3–5 (16%; n = 10) and 6–10 (3%, n = 2) additional days postoperatively. There was wide variation in both techniques of circumcision as well as adjuvant haemostatic agents used. Only 22% of respondents said that they had an established protocol for management of circumcision in the newborn haemophilia patient. These survey results highlight the need for evidence‐based guidelines regarding the optimal management of circumcision in neonates with severe haemophilia.